Characteristics and sources of ambient refractory black carbon aerosols: Insights from soot particle aerosol mass spectrometer. (July 2018) - Wang, Junfeng; Wu, Yangzhou; Ge, Xinlei; Shen, Yafei; Ge, Shun; Chen, Mindong
Abstract: This short communication investigated the characteristics and sources of refractory black carbon ( r BC) aerosols using an Aerodyne soot-particle aerosol mass spectrometer (SP-AMS). The SP-AMS dataset acquired at suburban Nanjing observed carbon clusters ( C n + ) up to n = 160, which was classified into three groups (low-C: C 1 + -C 5 + ; mid-C: C 6 + -C 31 + ; full-C (fullerenes): C 32 + -C 160 + ). A simple method was first developed to reduce influences of organic molecules on the C n + signals. We found that the temporal variations of low-C and mid-C varied similarly, but were substantially different from full-C, indicating different source contributions. Furthermore, positive matrix factorization analyses showed that the C 1 + /C 3 + ratios of traffic-, industry-, cooking-related r BC were 0.88, 1.29 and 0.01, respectively. We propose such C 1 + /C 3 + ratios can be used as references to distinguish different sources for r BC in ambient conditions, yet further verifications with more field data are still required, and whether or not such ratios in r BC cores are stable upon atmospheric ageing remains to be elucidated.